2022
DOI: 10.1002/cam4.5257
|View full text |Cite
|
Sign up to set email alerts
|

The need to tailor the omission of axillary lymph node dissection to patients with good prognosis and sentinel node micro‐metastases

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Twenty-two studies reported overall survival data ( 5 , 7 , 11 , 15 27 , 29 , 30 , 32 , 33 , 35 ). Eleven studies reported disease-free survival data ( 5 , 7 , 11 , 15 , 23 , 30 35 ). Six studies analyzed locoregional recurrence ( 21 , 26 , 28 , 35 , 36 ), and eight studies reported axillary recurrence ( 11 , 22 , 24 , 26 , 30 , 32 , 33 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two studies reported overall survival data ( 5 , 7 , 11 , 15 27 , 29 , 30 , 32 , 33 , 35 ). Eleven studies reported disease-free survival data ( 5 , 7 , 11 , 15 , 23 , 30 35 ). Six studies analyzed locoregional recurrence ( 21 , 26 , 28 , 35 , 36 ), and eight studies reported axillary recurrence ( 11 , 22 , 24 , 26 , 30 , 32 , 33 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…The NOS was used to assess the quality of evidence in non-RCT trials. Five studies received a rating of seven or more stars, indicating high quality ( 15 , 16 , 19 , 21 , 35 ).Seven studies received a rating of six stars ( 11 , 20 , 22 , 23 , 26 , 34 , 36 ), and six studies were assessed as having four to five stars (See Table 1 ). The GRADEpro GDT tool was used to classify the evidence of RCTs comparing ALND to SLNB alone for patients with clinical node-negative early-stage breast cancer and positive sentinel lymph nodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation